Application of diffusion dialysis MOF composite membrane in separation of HCl and AlCl3
By uniformly distributing MOF on the polymer film, a diffusion dialysis MOF composite film is formed, and the problem of low acid recovery and metal ion separation efficiency in the prior art is solved, and efficient and low-cost acid recovery and metal recovery effects are achieved.
Patent Information
- Application Number
- CN202411564104.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing commercial diffusion dialysis membranes have problems of low efficiency, high cost and poor mechanical properties in acid recovery and metal ion separation.
A diffusion dialysis MOF composite membrane is used, which consists of a polymer film as the substrate, and the MOF is evenly distributed on its surface, and efficient acid recovery and metal ion separation are achieved using the functional groups and pore structure of MOF.
High acid recovery rate (up to 81%) and high metal recovery rate (up to 90%) are achieved, while good mechanical properties and low production costs.
Smart Images

Figure CN119549006A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of membrane technology, and in particular to application of a diffusion dialysis MOF composite membrane in the separation of HCl and AlCl3. Background Art
[0002] With the energy shortage, resource shortage and serious environmental pollution, environmental protection has become a global issue and has attracted the attention of the whole society and mankind. A large amount of acidic waste liquid is generated in the industrial production process, which contains metal ions and useful acids of different concentrations. Harmless disposal not only wastes resources, but also brings secondary environmental and space problems. The implementation of clean production with efficient separation not only produces environmental benefits but also creates good economic and social benefits. Therefore, it is essential to recycle and reuse acidic waste liquid.
[0003] Waste acid recovery is an environmental protection work with high technical requirements, large economic investment and complex management. In order to overcome these difficulties, it is necessary to continuously develop more efficient and low-cost recovery technologies to promote the resource utilization and harmless treatment of waste acids. There are many types of waste acids, each with different characteristics and composition, which need to be treated in a targeted manner. Therefore, it is crucial to propose a research on the resource utilization of the generated waste acids.
[0004] Waste acid mainly includes waste hydrochloric acid, waste sulfuric acid, waste nitric acid, waste phosphoric acid, waste hydrofluoric acid, heavy metal salts, etc. The current methods for treating such wastes include neutralization, extraction, evaporation, electrodialysis, diffusion dialysis, etc. Most methods are economically unfeasible due to the high energy cost and large capital investment. For example, the method of recovering acid by evaporating sulfuric acid-containing waste includes concentrating free acid, removing sulfate, and decomposing sulfate. In contrast, diffusion dialysis based on anion exchange membranes provides an attractive method for treating such wastes. In addition to recovering metal ions and water, this method can also recover acid, so it is considered to be a cleaner, energy-saving and low-cost technology. It has been widely used in the recovery of inorganic acids such as hydrochloric acid (HCl), sulfuric acid (H2SO4), nitric acid (HNO3) and some organic acids.
[0005] In view of the characteristics of acidic wastewater, anion exchange membrane diffusion dialysis provides an attractive acid recovery method from the perspective of energy saving. Diffusion dialysis refers to the use of ion exchange membranes to separate feed liquids and receiving liquids of different concentrations. The solute diffuses from the high-concentration side through the membrane to the low-concentration side. When the concentrations on both sides of the membrane reach equilibrium, the dialysis process stops. The concentration difference is the driving force of dialysis. In addition to relying on the adsorption of individual components on the membrane, diffusion dialysis also mainly relies on the difference in diffusion coefficients of acids and salts in the membrane. Anion exchange membranes are the key to achieving this goal. Anion exchange membranes for diffusion dialysis are different from anion exchange membranes for electrodialysis. They are stable in acidic media, have good diffusivity for protons, and have good retention for other cations. They rely on the huge difference in diffusion rates between acids and salts. At present, there are few types of commercial diffusion dialysis membranes in industrial production, and there are problems such as high prices, low acid recovery efficiency, and low metal ion retention rates. Therefore, there is an urgent need to develop an industrially viable monovalent ion selective separation membrane, which needs to have high selective permeability, simple preparation process, low production cost and good mechanical properties.
[0006] Metal-organic framework (MOF) is a new type of crystalline material with high porosity, elastic pore properties, and large functional groups on the surface of MOF that can make it charged. MOF with functional groups can achieve attraction / repulsion of target ions in water treatment. Therefore, when MOF is prepared into a membrane, H with high activity, low charge, and small radius + Can quickly pass through the MOF membrane.
[0007] Chinese patent CN 103962020 A discloses a diffusion dialysis membrane (anion exchange membrane) for acid recovery, and its preparation method and application. The prepared diffusion dialysis membrane is composed of polyvinyl alcohol (PVA) grafted epoxy crystal salt and an anion-containing compound with amino crystals. The ion exchange capacity is 0.58-1.15mmol / g, the acid dialysis coefficient is 0.01-0.021m / h, and the separation factor is 18.6-21. However, due to its high density and poor water permeability, the acid recovery efficiency is not high, and the membrane production process is complicated and not suitable for industrial production. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides the application of diffusion dialysis MOF composite membrane in the separation of HCl and AlCl3. The diffusion dialysis MOF composite membrane disclosed in the present invention has the characteristics of high acid recovery rate, so it can be used in the semiconductor industry, electroplating industry, and acid recovery in metal pickling.
[0009] The first object of the present invention is to provide a method for preparing a diffusion dialysis MOF composite membrane, comprising the following steps:
[0010] Adding metal salt and ligand into solvent to prepare MOF mother solution;
[0011] Putting the polymer membrane into MOF mother liquor, reacting on the surface of the polymer membrane to form MOF material, washing and drying to obtain the diffusion dialysis MOF composite membrane; the MOF material includes at least one of MOF-801, UIO-66, and UIO-66-COOH;
[0012] The structural formula of MOF-801 is:
[0013] The structural formula of UIO-66 is:
[0014] The structural formula of the UIO-66-COOH is:
[0015] In some embodiments of the present invention, the metal salt is one or more of zirconium chloride, zirconium nitrate, and zirconium dioxide.
[0016] In some embodiments of the present invention, the MOF mother solution is a homologous MOF seed crystal or a heterologous MOF seed crystal.
[0017] In some embodiments of the present invention, the ligand is one or more of terephthalic acid, aminobenzoic acid, fumaric acid, p-hydroxybenzoic acid, 2-aminobenzimidazole, and 3-amino-4-(pyridin-4-yl)benzoic acid.
[0018] In some embodiments of the present invention, the molar ratio of the ligand to the metal salt is 5 to 100:1.
[0019] In some embodiments of the present invention, the solvent is selected from an organic solvent and / or water.
[0020] In some embodiments of the present invention, the organic solvent is selected from one or more of methanol, ethanol, and N,N-dimethylformamide.
[0021] In some embodiments of the present invention, the polymer in the polymer film is a porous high molecular polymer; the conditions of the surface reaction are: the reaction temperature is room temperature (25° C. to 40° C.), and the reaction time is 12h-72h.
[0022] In some embodiments of the present invention, the porous high molecular polymer is one or more of polyacrylonitrile, polypropylene, polyvinylidene fluoride, polyethylene, such as polyacrylonitrile film, polypropylene film, polyvinylidene fluoride film, polyethylene, etc.
[0023] The second object of the present invention is to provide a diffusion dialysis MOF composite membrane obtained by the preparation method. The water content of the diffusion dialysis MOF composite membrane is 150%, the acid recovery rate is 81%, and the metal recovery rate is 90%; the MOF material is ZIF-8, UIO-66, MOF-801, and UIO-66-COOH.
[0024] The third object of the present invention is to provide the diffusion dialysis MOF composite membrane for acid recovery.
[0025] The fourth object of the present invention is to provide the diffusion dialysis MOF composite membrane for the separation of HCl and AlCl3.
[0026] The above technical solution of the present invention has the following advantages compared with the prior art:
[0027] The diffusion dialysis MOF composite membrane proposed in the present invention aims to solve the problem that the commercial polyethylene / polypropylene membrane in the prior art has high mechanical strength and flexibility, but its acid recovery efficiency and metal recovery rate performance are average; the diffusion dialysis MOF composite membrane is a membrane composed of a polymer membrane as a base membrane and MOF uniformly distributed on its surface. The large functional groups on the surface of MOF can make it charged, and MOF with functional groups can achieve attraction / repulsion of target ions in water treatment. Therefore, when MOF is prepared into a membrane, H with high activity, low charge, and small radius + It can quickly pass through the MOF membrane. On the other hand, the presence of organic ligands in MOF can enhance its compatibility with the polymer matrix compared with traditional inorganic particles. This method has the prospect of large-scale application, excellent mechanical properties, good stability, significant separation selectivity and high ion flux. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0029] Figure 1 This is a SEM image of the surface of the PE film purchased in Example 3 of the present invention;
[0030] Figure 2 This is a SEM image of the surface of the MOF-801@PE film prepared in Example 3 of the present invention;
[0031] Figure 3 This is a SEM image of the cross section of the PE film purchased in Example 3 of the present invention;
[0032] Figure 4 This is a SEM image of the cross section of the MOF-801@PE membrane prepared in Example 3 of the present invention;
[0033] Figure 5 This is the XRD image of the MOF-801@PE film prepared in Example 3 of the present invention;
[0034] Figure 6 This is a schematic diagram of the principle of the MOF diffusion dialysis membrane in an embodiment of the present invention;
[0035] Figure 7 It is a schematic diagram of the assembly of the diffusion dialysis equipment in an embodiment of the present invention. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0037] Example 1
[0038] This embodiment provides a MOF diffusion dialysis membrane, and the preparation method includes the following steps:
[0039] S1. Weigh 1.5 mmol ZrCl4 in a reactor, then add 3 mL formic acid, stir with a magnetic force at 600 rpm for 1 minute, then gradually introduce 8 mL distilled water into the reactor, and ultrasonicate until the solution is evenly dispersed. Continue to stir with a magnetic force while adding 1.5 mmol terephthalic acid to the solution to obtain a mother solution of UIO-66-COOH.
[0040] S2. Soak the purchased PAN membrane in deionized water for 2 h.
[0041] S3. Transfer the UIO-66-COOH mother solution to a glass bottle, place the PAN membrane with the surface facing upward vertically into the UIO-66-COOH mother solution, and leave it at room temperature for 72 hours. The solution becomes very turbid within 72 hours, and then the PAN membrane is taken out, and the PAN surface changes from white to milky white, indicating that UIO-66-COOH has formed on the PAN membrane surface.
[0042] S4. The prepared membrane was rinsed with anhydrous ethanol and dried in a vacuum oven at 60°C to obtain a diffusion dialysis UIO-66-COOH@PAN membrane.
[0043] Example 2
[0044] This embodiment provides a MOF diffusion dialysis membrane, and the preparation method includes the following steps:
[0045] S1. Weigh 1.5 mmol ZrCl4 in a reactor, then add 3 mL formic acid, stir with a magnetic force at 600 rpm for 1 minute, then gradually introduce 8 mL distilled water into the reactor, and ultrasonicate until the solution is evenly dispersed. Continue to stir with a magnetic force while adding 1.5 mmol terephthalic acid to the solution to obtain a mother solution of UIO-66-COOH.
[0046] S2. Soak the purchased PE film in deionized water for 2 hours.
[0047] S3. Transfer the UIO-66-COOH mother solution to a glass bottle, place the PE film surface vertically upward into the UIO-66-COOH mother solution, and leave it at room temperature for 72 hours. The solution becomes very turbid within 72 hours, then take out the PAN film, and the PE surface changes from white to milky white, indicating that UIO-66-COOH has formed on the PE film surface.
[0048] S4. The prepared membrane was rinsed with anhydrous ethanol and dried in a vacuum oven at 60°C to obtain a diffusion dialysis UIO-66-COOH@PE membrane.
[0049] Example 3
[0050] This embodiment provides a MOF diffusion dialysis membrane, and the preparation method includes the following steps:
[0051] S1. Weigh 1.5 mmol ZrCl4 and 2 mL formic acid, stir magnetically at 600 rpm for 1 minute, then gradually introduce 8 mL distilled water and 5 mL dimethylformamide (DMF) into the reactor, and then ultrasonicate until the solution is uniformly dispersed. Continue to stir magnetically while adding 1.5 mmol fumaric acid to the solution to obtain the mother solution of MOF-801.
[0052] S2. Soak the purchased PE film in deionized water for 2 hours.
[0053] S3. Transfer the MOF-801 mother solution to a glass bottle, place the PE film vertically upward into the MOF-801 mother solution, and let it stand at room temperature for 12 hours. The solution becomes very turbid within 12 hours, and then the PE film is taken out, and the PE surface changes from white to yellow, indicating that MOF-801 (Zr) has formed on the PE film surface.
[0054] S4. The obtained membrane was rinsed with anhydrous ethanol and dried in a vacuum oven at 60°C to obtain a diffusion dialysis MOF-801@PE membrane. The obtained MOF-801@PE membrane was structurally characterized. The SEM image of the surface of the obtained MOF-801@PE membrane is shown in FIG. Figure 2As shown in the figure, the surface of the PE membrane is evenly covered with small balls, which proves the successful loading of MOF-801 on the PE membrane. The SEM image of the cross section of the prepared MOF-801@PE membrane is shown in Figure 4 As shown in the figure, it can also be clearly seen from the cross-sectional view that a layer of MOF-801 is covered on the PE film, indicating the successful preparation of the MOF composite membrane.
[0055] Example 4
[0056] This embodiment provides a MOF diffusion dialysis membrane, and the preparation method includes the following steps:
[0057] S1. Weigh 1.5 mmol ZrCl4 and 5 mL formic acid, stir with magnetic force at 600 rpm for 1 minute, then gradually introduce 10 mL distilled water and 3 mL dimethylformamide (DMF) into the reactor, and then ultrasonicate until the solution is uniformly dispersed. Continue to stir with magnetic force while adding 1.5 mmol aminobenzoic acid to the solution to obtain the mother liquor of UIO-66.
[0058] S2. Soak the purchased PE film in deionized water for 2 hours.
[0059] S3. Transfer the UIO-66 mother solution to a glass bottle, place the PE film surface vertically upward into the UIO-66 mother solution, and leave it at room temperature for 24 hours. The solution becomes very turbid within 24 hours, then take out the PE film, and the PE surface changes from white to milky white, indicating that UIO-66 (Zr) has formed on the PE film surface.
[0060] S4. The prepared membrane was rinsed with anhydrous ethanol and dried in a vacuum oven at 60°C to obtain a diffusion dialysis UIO-66@PE membrane.
[0061] Comparative Example 1
[0062] This comparative example proposes a polymer diffusion dialysis membrane. The polymer membrane used is a commercially purchased PAN membrane. The purchased PAN membrane is soaked in deionized water for 2 hours.
[0063] Comparative Example 2
[0064] This comparative example proposes a polymer diffusion dialysis membrane. The polymer membrane used is a commercial membrane purchased. The purchased PE membrane is soaked in deionized water for 2 hours. The SEM image of the surface of the purchased PE membrane is as follows: Figure 1 As shown in the figure, the pore size of the PE membrane surface is large and fibrous. Solution ions can easily pass through the large pores. The SEM image of the purchased PE membrane cross section is as follows: Figure 3 As shown, compared to Figure 2 , Figure 3 It also shows the smoothness of the PE film, and solution ions are not easily adsorbed on its surface.
[0065] Testing of Diffusion Dialysis Acid Recovery Application
[0066] Cut a rectangular piece of film sample obtained in the embodiment and comparative example, the area of the sample ranges from 28 to 35 cm 2 , where the area used for diffusion dialysis is 30cm 2 . The membrane sample is fixed in the center of a pool containing two compartments. The volume of solution that can be added to each compartment is 100mL. One compartment is used as a feed chamber, which is filled with a diffusion liquid with a composition of 2.5mol / L HCl and 0.1mol / LAlCl3. The other pool is used as a diffusion chamber, which is filled with pure water. Before the test, the membrane is pre-soaked in the feed liquid for 24 hours. During the diffusion test, a water bath device is used to control the temperature of the solution in the two compartments to 25°C; at the same time, a peristaltic pump is used to circulate the solution in the two compartments to eliminate the concentration polarization effect. The flow rate between the two compartments is 1:1.12 (where the unit of flow rate is L / (m 2 h)). After 120 min of diffusion, the solution in the diffusion chamber and the material chamber was taken out, and the concentration of HCl was calibrated with Na2CO3 solution using methyl orange as an indicator, and the concentration of AlCl3 was determined by complexometry with EDTA. Total acid recovery rate ηH + ,ηAl 3+ It can be calculated by the following formula: ηi=C di Q d / C fi Q f =1 / 1+(C ri Q r / C di Q d ), where C di , C ri , C fi are the concentrations of component i in the diffusion fluid, dialysate, and feed, respectively. d , Q r , Q f are the flow rate intensities of the diffusion fluid, dialysate and feed, respectively.
[0067] The diffusion and permeability performance of the MOF composite membrane materials of Examples 1-4 and the polymer membranes of Comparative Examples 1-2 were tested, and the test results are shown in Table 1.
[0068] Table 1 Comparison of the performance of the diffusion dialysis membrane of the present invention
[0069]
[0070] From the test data of the above examples and comparative examples, it can be seen that under the same experimental conditions, the acid recovery rate of the commercial membrane purchased in Comparative Examples 1 and 2 is only about 40%. In comparison, the acid recovery performance of Examples 1-4 of in-situ grown MOF materials has been improved by 40%. This is because the large functional groups on the surface of MOF can make it charged, and MOF with functional groups can achieve attraction / repulsion of target ions in water treatment. Therefore, when MOF is prepared into a film, H with high activity, low charge, and small radius + can quickly pass through the MOF membrane. On the other hand, the uniform growth of MOF also effectively reduces the pore size of the membrane in the comparative example, and more A l3+ cannot be blocked on the film surface, so Al 3+ Improved interception rate, Figure 1 and Figure 2 This shows that among Examples 1-4, the acid recovery rate and metal retention rate of Example 3 are the highest, because this MOF has a one-dimensional (1D) diamond channel along the a-axis. The clusters and ligands make the one-dimensional channel have hydrophilic sites, which accelerates the H + The pore size of this MOF is also the smallest, so it can be dispersed more densely on the PE membrane, hindering the movement of Al 3+ This shows that the MOF mixed matrix membrane of the present invention has excellent performance and great potential in the field of acid recovery.
[0071] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. Application of a diffusion dialysis MOF composite membrane in the separation of HCl and AlCl3; the diffusion dialysis MOF composite membrane is prepared by the following method, characterized in that: The following steps are involved: Adding metal salt and organic ligand into a solvent to prepare MOF mother solution; Putting the polymer membrane into the MOF mother solution, reacting on the surface of the polymer membrane to form MOF material, washing and drying to obtain the diffusion dialysis MOF composite membrane; The MOF material includes at least one of MOF-801, UIO-66, and UIO-66-COOH; The structural formula of MOF-801 is: The structural formula of UIO-66 is: The structural formula of the UIO-66-COOH is:
2. The use according to claim 1, characterized in that: The metal salt is one or more of zirconium chloride, zirconium nitrate or zirconium dioxide.
3. The use according to claim 1, characterized in that: The MOF mother solution is a homologous MOF seed crystal or a heterologous MOF seed crystal.
4. The use according to claim 1, characterized in that: The organic ligand is one or more of terephthalic acid, aminobenzoic acid, fumaric acid, p-hydroxybenzoic acid, 2-aminobenzimidazole, and 3-amino-4-(pyridin-4-yl)benzoic acid.
5. The use according to claim 1, characterized in that: The molar ratio of the organic ligand to the metal salt is 5 to 100:
1.
6. The use according to claim 1, characterized in that: The solvent is selected from organic solvents and / or water.
7. The use according to claim 1, characterized in that: The polymer in the polymer film is a porous high molecular polymer.
8. The use according to claim 1, characterized in that: The conditions of the surface reaction are as follows: the reaction temperature is 25°C-40°C, and the reaction time is 12h-72h.
Citation Information
Patent Citations
Anion exchange driven cation selective separation hybrid membrane as well as preparation and application thereof
CN114471177A
Mixed matrix membrane for acid diffusion dialysis as well as preparation method and application of mixed matrix membrane
CN114618307A
MOF-801 separation membrane containing mixed ligand, preparation method and application of MOF-801 separation membrane in alcohol-water separation
CN117815930A
Process for the preparation of mofs-porous polymeric membrane composites
US20150367294A1